Malaria and Agricultural Production in Nigeria - Udoudo, Mosunmola Grace Moses; Umoh, Gabriel Sunday; Akpaeti, Aniekan Jim (Asian Development Policy Review, 2016)
Malaria has adverse effect on agricultural production in Nigeria. This study examined the effect of malaria morbidity on the agricultural Gross Domestic Product (GDP) in Nigeria as well as predicts the future incidence of malaria in Nigeria. Secondary data employed in the study were analyzed using descriptive statistics, production function and Markov chain analysis. Findings from the study revealed that the highest percentage change in malaria morbidity and mortality were recorded in the period between 1996 and 2000 just before the Millennium Development Goal declaration. Malaria impacted negatively on agriculture production in the country both in the short and long-run. For every one reported case of malaria per 100,000 persons in the country, while holding other explanatory variables constant, Agric. GDP will reduce by N 0.762 per year. Projections of malaria morbidity in Nigeria revealed that by the end of the year 2040, the number of people that will die of malaria for every reported case will increase. The paper recommends that efforts should be directed towards the complete extermination of malaria vectors.